Investigation on Human Development Needs, Challenges, and Drivers for Transition to Sustainable Development: The Case of Qatar - Btool H. Mohamed (19504939) (2022)
Human development has been widely accepted as both the primary goal and driver of sustainable development. Human development is critically important for countries attempting a radical transformation from a resource-based economy to knowledge-based, sustainable development, like Qatar. This paper examines Qatar’s human development needs and challenges with respect to its economic, demographic, and educational development goals. Following a comprehensive literature review, domain-specific documentary information and data were collected and analyzed, along with qualitative insights and data obtained through semi-structured interviews with local professionals from various sectors, to gather opinions about the needs, challenges, drivers, and recommendations for human development. A preliminary integrated policy framework and set of recommendations for human development planning are proposed as a guide, for Qatar and similar countries, for transitioning from a resource-based economy to knowledge-based sustainable development. This framework and the understanding of the needs, challenges, and drivers based on the qualitative research, in conjunction and in comparison with the literature analysis, are expected to assist decision-makers in devising, and more importantly implementing, tailored policies and roadmaps focused on four key dimensions: skills (education), citizenship, leadership, and health. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su14063705